The Role of the Doctrine of Jawā’iḥ in Economic Crises: In the Light of Islamic Jurisprudential Principles: معاشی بحرانوں میں نظریۃ الجوائح کا کردار: اسلامی فقہی اصولوں کی روشنی میں - Irfan, Dr. Muhammad; Majid , Dr. Abdul; Khan, Shamshir (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Islamic Shariah has provided various principles and regulations to address the impacts of emergencies on financial transactions and to minimize potential losses. If transactions are carried out in accordance with these principles, neither the seller incurs a loss nor does the buyer suffer. The classical jurists generally limited the rulings related to such emergency situations to the sale and purchase of fruits and vegetables. However, in the present era, various types of contracts that emerge under modern circumstances can also be conducted in light of the concessions granted for such emergencies. For instance, in the modern banking system, contracts like Salam, Istisna‘, and Ijarah, as well as other contract-related financial matters faced by financial institutions, can be resolved within the framework of the exemptions provided under emergency conditions.